2021
DOI: 10.25273/counsellia.v11i1.8882
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Permainan Ular Tangga Keyakinan dalam Peningkatan Efikasi Diri Siswa SMP

Abstract: <p>The purpose of this research is to develop a game media of Snakes and Ladder of Faith which is effective for increasing the self-efficacy of students at SMP Negeri 2 Krian. This research and development method uses a research and development procedure with the following steps: 1) preliminary study, 2) media development, and 3) media testing. Based on the material expert's assessment, an average score of 0.46 was obtained which was categorized as quite feasible. Based on the media expert's assessment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
(6 reference statements)
0
3
0
4
Order By: Relevance
“…The description above is supported by research that has been conducted by Wulandari & Pravesti (2021), who found that the game of snakes and ladders of belief can effectively be used to increase students' academic self-efficacy through pre-posttest results and treatment using these media. UNO card game media can develop student character (Septyani et al, 2021).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The description above is supported by research that has been conducted by Wulandari & Pravesti (2021), who found that the game of snakes and ladders of belief can effectively be used to increase students' academic self-efficacy through pre-posttest results and treatment using these media. UNO card game media can develop student character (Septyani et al, 2021).…”
Section: Introductionmentioning
confidence: 82%
“…According to the research conducted by Ardiansyah & Pravesti (2021), monobilling media experiences significant effectiveness in increasing academic self-efficacy in high school students, meaning that the media is effective to use. Supported by the research of Wulandari & Pravesti (2021), the snake and ladder game media is effective and appropriate to use based on media expert tests and can increase student self-efficacy. The Self-Efficacy Wheel game media is suitable for use in providing guidance and counseling services and is effective for increasing self-efficacy in high school students (Kristanti & Pravesti, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Group counselling is a method that has been proven effective in helping individuals overcome psychological problems and improve their mental well-being (Prabowo, 2020;Utamy et al, 2021;Wulandari, 2020). Meanwhile, cognitive reconstruction techniques are a cognitive-behavioural approach that has proven effective in changing negative thought patterns into positive ones and helping individuals respond to situations more adaptively (Kara et al, 2023;Seligman & Reichenberg, 2010;Short & Thomas, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Teori Perkembangan Sosial Emosional menyatakan bahwa aktivitas di luar ruangan (Ndari et al, 2019) dapat membantu dalam perkembangan sosial dan emosional anak (Azizah & Busyra, 2021). Teori Self-Determination menyatakan bahwa aktivitas yang menyenangkan dan menarik bagi anak akan lebih efektif dalam meningkatkan perkembangan gerak anak (Wulandari, 2020). Teori Belajar Melalui Permainan (Veronica, 2018) menyatakan bahwa permainan di luar ruangan (Nurmalitasari, 2015) dapat membantu dalam perkembangan kognitif dan motorik anak (Fadlillah, 2019).…”
Section: Pendahuluanunclassified